INFORMATION AND COMMUNICATION TECHNOLOGIES IN GEOGRAPHICAL EDUCATION AND THE CONSTRUCTION OF TERRITORIAL CITIZENSHIP AND YOUTH PROTAGONISM - Cruz Barbosa Vieira, Emanuella (Revista Gênero e Interdisciplinaridade, 2021)
The present research aims to analyze the use of Information and Communication Technologies (ICT) in Geographic Education as an important tool in the development of citizenship, meaningful learning and youth protagonism, allowing the construction of more motivating teaching/learning experiences, bringing schools closer to interests. of students, we sought to understand how the use of ICT provides the construction of territorial citizenship from a perspective of appropriation and intervention in the local space. For this, the project We Propose: Citizenship and Innovation in Geographic Education at the University of Lisbon and the Nucleus of Work, Research and Social Practices (NTPPS), developed by the Department of Education of the State of Ceará, both worked in association at the University of Lisbon, were analyzed. High School Dona Hilza Diogo de Oliveira, in Fortaleza, Ceará.